The principles of digital transformation for development (DX4D): Systematic literature review and future research agenda - Richard Heeks; Bookie Ezeomah; Gianluca Iazzolino; Aarti Krishnan; Rose Pritchard; Jaco Renken; Qingna Zhou (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
Given the growing salience of digital transformation within international development, this paper presents the results of a systematic literature review on “digital-transformation-for-development” (DX4D). Using a variety of different search terms, a corpus of 75 papers was analysed. This paper presents general features of the literature and the research designs used. The main analysis consists of 13 principles that can be used as a starting point to guide a better understanding and operationalisation of digital-transformation-for-development research and consulting. The paper ends with a brief outline of future DX4D research priorities.
Keywords: 330; Systematic literature review; Digital transformation for development (DX4D); International development strategies; DX4D principles and guidelines; Future research priorities in DX4D